2017
DOI: 10.1111/1759-7714.12483
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of pemetrexed and concurrent radiotherapy for previously untreated elderly patients with locally advanced non‐squamous non‐small cell lung cancer

Abstract: BackgroundChemoradiotherapy is the standard treatment for locally advanced non‐small cell lung cancer (NSCLC); however, it is disputed whether this treatment is suitable for patients aged ≥75. This study was conducted to determine the maximum tolerated dose (MTD) of pemetrexed for use in concurrent radiotherapy for elderly patients with locally advanced non‐squamous NSCLC.MethodsThe eligibility criteria were as follows: aged ≥75 with inoperable stage IIIA or IIIB non‐squamous NSCLC, no history of chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, the response rate of 66.7% is comparable with that of other studies, and the median overall survival was >5 years. Recently, Takemoto et al reported the results of a Phase I dose escalation study similar to ours in elderly patients with LA-NSCLC [12]. In their study, two patients were enrolled at pemetrexed Dose Level 1 (400 mg/m 2 ); however, one patient, who experienced prolonged leukopenia and chemoradiotherapy, was discontinued on Day 35.…”
Section: Discussionmentioning
confidence: 67%
“…However, the response rate of 66.7% is comparable with that of other studies, and the median overall survival was >5 years. Recently, Takemoto et al reported the results of a Phase I dose escalation study similar to ours in elderly patients with LA-NSCLC [12]. In their study, two patients were enrolled at pemetrexed Dose Level 1 (400 mg/m 2 ); however, one patient, who experienced prolonged leukopenia and chemoradiotherapy, was discontinued on Day 35.…”
Section: Discussionmentioning
confidence: 67%
“…It is interesting to note that single-agent amrubicin treatment in elderly patients was not a risk factor in the present study, whether they were 65 years or older or 75 years or older. Although chemotherapy in elderly patients is known to have different results than in younger patients [ 32 , 33 , 34 ], it is presumed that chemotherapy can safely be administered to even elderly patients with good PS and an appropriate dose setting. An amrubicin dose of 45 mg/m 2 was a factor for longer OS, and decrease in dose before treatment was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited clinical information about patients harboring BRAF mutations, especially in elderly patients and those with poor PS, because BRAF mutations are only found in a few populations. Intensive treatment, such as combination chemotherapy or combined modality, does not usually produce a survival benefit in patients aged >70 or 75 years 12–14 . On the other hand, the use of therapies targeting other driver oncogenes is recommended, regardless of the patient's age and general condition, because of the marked responses they induce and their mild toxicities 15–17 .…”
Section: Discussionmentioning
confidence: 99%
“…Intensive treatment, such as combination chemotherapy or combined modality, does not usually produce a survival benefit in patients aged >70 or 75 years. [12][13][14] On the other hand, the use of therapies targeting other driver oncogenes is recommended, regardless of the patient's age and general condition, because of the marked responses they induce and their mild toxicities. [15][16][17] However, the patient in the present case was 86 years old, which is classified as "oldest old", and the supportive care rates in this age group range from 55%-67%.…”
Section: Discussionmentioning
confidence: 99%